The Relationship Between the Quality of Services Provided and the Level of Blood Pressure in Hypertensive Patients in Bangkok Metropolitan - Choosanuk, Pichaya; Koshakri, Rukchanok; Meekusol, Saovaros (Journal of The Royal Thai Army Nurses, 2025)
This research was a descriptive correlational study of quality variables of care service process and blood pressure levels of hypertensive patients in Bangkok. To study the relationship of the quality of receiving care services that consist of health promotion. prevention of complications and continuation of care with health outcomes, including blood pressure levels Using Donabedian’s quality of care concept, the samples were patients with hypertension in Bangkok. Both males and females, aged 18 years and over, not limited to blood pressure levels, who have been admitted to the public health center for at least 1 year in 12 communities, totaling 137 cases using a simple random sampling method. Data were collected between March 2022 and August 2022 using questionnaires, namely the general information questionnaire and the quality of receiving care services for hypertension. Data were analyzed using descriptive statistics and correlation was analyzed by Pearson’s correlation coefficient. The results showed that receiving health promotion care services complication prevention and continuous care care was significantly negatively associated with systolic and diastolic blood pressure levels (r = -.536, -.402 and -.464 , p < .01 respectively) (r = -.289, -.221 and -.321, p < .01 respectively) can be used as basic information to develop guidelines for improving the quality of service provision in the care of hypertension patients for better efficiency and effectiveness.